Analisis Karakteristik Aerodinamis Airfoil Simetris Dan Airfoil Camber Pada Turbin Angin Poros Vertikal Jenis Helix - Saepulloh Aditya; Maria F. Soetanto (Politeknik Negeri Bengkalis, 2021)
This journal discusses the airfoil simulation on a helix type vertical turbine blade. The airfoils used are NACA 0018 and 4418. The simulation uses a Computational Fluid dynamics (CFD) application. In this simulation, TSR values are entered starting from 3.5, 3.8, 4.1, 4.4, 4.7, 5.0, 5.3, 5.6, 5.9, 6.2, 6.5. The results of the simulation show that the highest inhibition coefficient value is at TSR = 5.3 with a value = 1.631 and for NACA 0018, and for NACA 4418, the highest inhibition coefficient value is at TSR 6.5 with a value = 1.582. In the calculation results, the highest drag force (Fd) is at TSR 3.5 of 0.678 Newton at NACA 0018 with a turbine power of 10.78 Watt with a value of = 0.35, turbine efficiency 35%.Keywords : Airfoil, TSR, NACA, TASV, CFD